Indopiptadenia oudhensis (Brandis) Brenan - An Endangered Tree Legume of Uttar Pradesh and Nepal - Biswas, S.A.S.; Chandra, Sumer (Indian Forester, 1997)
Taxonomic status of Indopiptadenia oudhensis (Brandis) Brenan, a monotypic taxon typically of American and African origin has been elucidated with particular emphasis on distribution, phenology and measures proposed for conservation.